2020
DOI: 10.7150/jca.40358
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant transarterial chemoembolization following radical resection for intrahepatic cholangiocarcinoma: A multi-center retrospective study

Abstract: Background and Aims: The prognosis of intrahepatic cholangiocarcinoma (ICC) after radical resection is far from satisfactory, but the effect of postoperative transarterial chemoembolization (p-TACE) remains controversial. This multi-center retrospective study was to evaluate the clinical value of p-TACE and identify the selected patients who would benefit from p-TACE. Methods: Data of ICC patients who underwent radical resection with/without p-TACE therapy was obtained from 12 hepatobiliary centers in China be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
(56 reference statements)
0
12
0
Order By: Relevance
“…Systemic chemotherapy combined with local therapy can significantly improve patient prognosis. Intra-arterial therapies combined with chemotherapy can shrink the lesion to achieve R0 resection[ 34 ]. In this study, the median survival of 3 patients with recurrent ICC treated with TACE combined with the GEMOX regimen was 5 mo, which was longer than that of patients with recurrent ICC using chemotherapy alone (median OS, 4 mo).…”
Section: Discussionmentioning
confidence: 99%
“…Systemic chemotherapy combined with local therapy can significantly improve patient prognosis. Intra-arterial therapies combined with chemotherapy can shrink the lesion to achieve R0 resection[ 34 ]. In this study, the median survival of 3 patients with recurrent ICC treated with TACE combined with the GEMOX regimen was 5 mo, which was longer than that of patients with recurrent ICC using chemotherapy alone (median OS, 4 mo).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the literature search strategy, 1,684 records of study were identified. After duplicate removal, title and abstract review, and full-text reading, a total of eleven studies [23][24][25][26][27][28][29][30][31][32][33] with 2,757 patients were finally included in the study. A flow diagram of the study search and selection process is shown in Fig.…”
Section: Study Selection and Clinical Characteristicsmentioning
confidence: 99%
“…Almost all included studies were published in English and only one study was published in Chinese [23]. Six studies [24,26,[28][29][30]33] considered the effect of MVI on ICC, and one of the studies [33] only performed postoperative adjuvant TACE after hepatectomy in ICC patients with MVI. Ten studies [23-30, 32,33] and seven studies [23,24,26,29,30,32,33] reported LNM and multifocal ICC tumor, respectively.…”
Section: Study Selection and Clinical Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another multicentric retrospective study between 2014 and 2017 analyzed 335 patients in 12 centers ( 50 ). The median OS of patients in the TACE plus surgery group was longer than that of patients in the surgery group (63 vs 18 months, P = 0.041).…”
Section: Interventional Treatment For Ccamentioning
confidence: 99%